2008
DOI: 10.1093/toxsci/kfn048
|View full text |Cite
|
Sign up to set email alerts
|

Heme-oxygenase 1 Gene Expression is a Marker for Hexavalent Chromium-Induced Stress and Toxicity in Human Dermal Fibroblasts

Abstract: Several adverse health effects, including irritant and allergic contact dermatitis, have been reported among workers who are occupationally exposed to chromium-containing compounds. Human dermal fibroblasts were used as an in vitro experimental model to study the potential mechanisms underlying hexavalent chromium [Cr(VI)]-induced dermal toxicity. Exposure of the fibroblasts to 5 microM Cr(VI) (LC50 for a 24-h exposure period) followed by microarray analysis of the gene expression profile revealed overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The cytotoxicity data obtained in the present investigation is in agreement with our previous report [1] and further supports the dermal toxicity potential of Cr(VI) [7]. Many of the genes that were differentially expressed in our previous study [1] were also found differentially expressed in the current study. However, quantitative differences in the expression of those genes were noticed between the two studies.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The cytotoxicity data obtained in the present investigation is in agreement with our previous report [1] and further supports the dermal toxicity potential of Cr(VI) [7]. Many of the genes that were differentially expressed in our previous study [1] were also found differentially expressed in the current study. However, quantitative differences in the expression of those genes were noticed between the two studies.…”
Section: Discussionsupporting
confidence: 93%
“…These results were essentially similar to those of our previous publication [1] and are, therefore, not presented here. Exposure of fibroblasts to 5 µM Cr(VI) for 16-hours (the time interval employed in the case of gene expression experiment) resulted in <30% cell death (data not presented).…”
Section: Cr(vi) Cytotoxicity In Human Dermal Fibroblastssupporting
confidence: 92%
See 3 more Smart Citations